2020
DOI: 10.1111/omi.12326
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans induces a proatherosclerotic response in human endothelial cells in a three‐dimensional collagen scaffold model

Abstract: The role of periodontopathogens in inflammatory endothelial dysfunction is not known. This study characterizes a three‐dimensional model with human coronary artery endothelial cells on three‐dimensional (HCAEC‐3D) type I collagen scaffolds to evaluate whether infection with Aggregatibacter actinomycetemcomitans induces a proinflammatory response associated with atherosclerosis. The HCAEC‐3D culture was physicochemically characterized with regard to biocompatibility and barrier function. Then, the culture was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In some cases, cells in Matrigel are used like vascular models, but this does not represent the structure on which the endothelial cells grow and form a monolayer in the endothelium vascular. The type I collagen scaffold provides a structure that promotes endothelial cells’ growth and monolayer formation and modulates their inflammatory response to LPS and bacteria from periodontopathogens [ 38 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, cells in Matrigel are used like vascular models, but this does not represent the structure on which the endothelial cells grow and form a monolayer in the endothelium vascular. The type I collagen scaffold provides a structure that promotes endothelial cells’ growth and monolayer formation and modulates their inflammatory response to LPS and bacteria from periodontopathogens [ 38 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that A. actinomycetemcomitans infection increased transforming growth factor beta 1, IL-8, MCP-1, and IL-6 secretion in HCAECs in a dose-dependent manner in a 3D model. This proinflammatory response stimulated the THP-1 monocyte activation, adhesion, and migration ( 94 ). Similarly, E. corrodens -LPS activates HCAECs pathway TLR4, ERK, and NF-kB p65, inducing a pro-atherosclerotic endothelial response and monocyte adhesion ( 95 ).…”
Section: Endothelial Dysfunction Mediated By Periodontopathic Microor...mentioning
confidence: 99%